The Impact of Online Game on the Children’s Character Change - Gek Diah Desi Sentana; I Wayan Nerta; I Gede Suwindia; I Putu Oka Agus Mahendradatta (Jurnal Penjaminan Mutu, 2019)
Online games are very fast growing lately. The longer, it becomes more fun, including the appearance, style of play, game graphics, image resolution, and so on. There is also a variety of player types such as war, adventure, strategy, fight and all types of online games which are surely interesting to play. The kind of technology development greatly impacts the development of the children's character. When technology is used positively, surely it will help us in our daily life and vice versa. Program (PKM), 1 title Village Partner Development Program (PPDM)